Experimental research on drying control condition with minimal effect on concrete strength. (15th March 2017) - Zhang, Guohui; Li, Zongli; Zhang, Linfei; Shang, Yujuan; Wang, Hang
Graphical abstract: Highlights: Compressive strength decreases and then increases with increase in temperature. Splitting tensile strength decreases with increase in drying temperature. Drying control condition with minimal effect was obtained on concrete strength. Components and defects of concrete after nondestructive drying was analyzed. Abstract: In order to obtain the drying control condition with no or minimal effect on concrete strength, various drying temperatures conditions are used as 150 °C, 120 °C, 105 °C, 85 °C and 60 °C, and the drying procedure of continuous and intermittent cyclic are presented independently in this study. The change of specimen mass is recorded in the drying process, and the compressive strength and splitting tensile strength are measured after the natural cooling. The results show that the concrete compressive strength initially decreases and then increases with the increase in drying temperature, while the splitting tensile strength always decreases. The relative compressive and splitting tensile strength of concrete in dry state are 1 and 0.99 respectively after 115.5 h of continuous drying at 105 °C, which denotes the optimal drying control condition has minimal effect on the strength, and efficiency is suitable. Finally, the change in components and defects structure of the concrete after minimal damage drying is analyzed through the thermo-gravimetric analysis, electron microscope scanning and industrial CT scanning.